2019
DOI: 10.1080/02713683.2019.1679839
|View full text |Cite
|
Sign up to set email alerts
|

Ranibizumab Pro Re nata versus Dexamethasone in the Management of Ischemic Retinal Vein Occlusion: Post-hoc Analysis from the COMRADE Trials

Abstract: Purpose: To compare ischemia-related clinical outcomes in patients treated with either ranibizumab pro re nata (PRN) or single dexamethasone implant in the Branch Retinal Vein Occlusion (COMRADE-B) or Central Retinal Vein Occlusion (COMRADE-C) trials. Methods: A post-hoc analysis of the Phase IIIb, 6-month, multicenter, double-masked, randomized, COMRADE-B and COMRADE-C trials. Change over 6 months in retinal ischemia status (central avascular [CA] zone and peripheral nonperfusion [PNP]), mean best-corrected v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Some studies have revealed that anti-VEGF drugs are effective for iCRVO eyes. Pielen et al [20] found that BCVA gain over six months in ranibizumab-treated RVO patients is not affected by ischemia, and is associated with less development of new ischemia during the first 6mo, but longterm observations are still lacking. Spooner et al [21] analyzed the 8-year outcomes of eyes with ischemic and non-ischemic RVO following treatment with a 3+PRN anti-VEGF regimen.…”
Section: Demographic and Clinical Characteristicsmentioning
confidence: 99%
“…Some studies have revealed that anti-VEGF drugs are effective for iCRVO eyes. Pielen et al [20] found that BCVA gain over six months in ranibizumab-treated RVO patients is not affected by ischemia, and is associated with less development of new ischemia during the first 6mo, but longterm observations are still lacking. Spooner et al [21] analyzed the 8-year outcomes of eyes with ischemic and non-ischemic RVO following treatment with a 3+PRN anti-VEGF regimen.…”
Section: Demographic and Clinical Characteristicsmentioning
confidence: 99%